Understanding Brettanomyces behaviour to optimise the use of alternatives to SO₂ in wines - Hart, Maria do Carmo Lupi Melbourne (2022)
Mestrado em Engenharia de Viticultura e Enologia / Instituto Superior de Agronomia. Universidade de Lisboa